INDUSTRIAL DIVERSIFICATION AND FIRM PERFORMANCE OF MANUFACTURING: DOES EFFICIENCY MATTER? - Rahmat Setiawan; riska agustin (Faculty of Economics and Business, University of Pasundan, 2018)
Industrial diversification is one of the important strategies in developing the firm’s market share which is expected to improve firm’s performance. When a firm wants to diversify the industry, it requires knowledge and efficiency of managers in managing the strategy so that it can increase the benefits of the existence of industrial diversification relationship with firm’s performance. This study aims to examine the effect of efficiency on the relationship between industrial diversification and firm’s performance in manufacturing companies in Indonesia. By using the purposive sampling method and the 2012-2016 study periods, we obtained data from 70 manufacturing companies with a total of 253 observations. We found that industrial diversification had a significant positive effect on firm’s performance. Efficiency as a moderating variable shows that efficiency strengthens the positive relationship of industrial diversification on firm performance.